Diversity and bioclimatic profiles of Vanilla spp. (Orchidaceae) in Mexico - Flores Jiménez, Álvaro (2017)
The genus Vanilla comprises around 110 species distributed throughout Earth's tropical regions, with the largest number of reported species growing in the American continent. Vanilla farming is associated with many Mexican cultures such as the Totonac, Mayan, Chinantec, and Mazatec, among others. Currently, this crop is threatened by technical, social, ecological, and climatic conditioning factors, limiting its production and the preservation of wild and cultivated species. It is therefore necessary to ascertain the current diversity status of each of these species, as well as some of their main bioclimatic profile indicators, in order to help decision-making, aimed at preserving and genetically improve these species. During 2008, we gathered data from IPN, MEXU, and XAL herbaria, as well as from CONABIO’s World Information Network on Biodiversity (REMIB), the Global Biodiversity and Information Facility (GBIF), and we also used data from live access to BUAP’s vanilla germplasm bank, obtained between 2008 and 2014. Distribution maps were generated using a geographical information system. Bioclimatic profiles for each species were obtained considering 19 WorldClim variables and altitude at a spatial resolution of approximately 1 Km2. Variance, Mean, and standard deviation for each of the 19 variables were calculated at each of the registered points. Extreme environmental condition intervals (minimum, average, and maximum) were also obtained. In order to determine the most important distribution variables of the species, we performed a principal component analysis and carried out Kruskal-Wallis and Dunn's tests on the variables identified as significant. Results indicated records for V. planifolia, V. pompona, V. insignis, V. inodora V. odorata, V. cribbiana, and V. sprucei in Mexico, distributed throughout nine states in the country. V. planifolia presented wide intervals of temperature and rain precipitation, while V. pompona, V. odorata, V. insignis and V. inodora presented intermediate intervals. The amplitudes of extreme data for each species can be considered in locating areas where ex situ regional preservation strategies could be put in place, as well as in establishing areas for cultivation. The bioclimatic profile we found, allows for an indirect inference of each species’ genetic condition, which could be used in genetic improvement programs; for instance, V. odorata grows at high altitudes and tolerates low temperatures, while V. inodora tolerates high temperatures, and V. odorata, V. pompona and V. planifolia tolerate low rain precipitation.